Serum cytokine profiles in healthy nonhuman primates are blunted by sedation and demonstrate sexual dimorphism as detected by a validated multiplex immunoassay - Laura Hocum Stone (Nature Portfolio, 2021)
Abstract Cytokine profiling is a valuable tool for monitoring immune responses associated with disease and treatment. This study assessed the impact of sex and sedation on serum cytokines in healthy nonhuman primates (NHPs). Twenty-three cytokines were measured from serum using a bead-based multiplex assay. Assay validation for precision, sensitivity, recovery, linearity, and stability was performed. Samples from male and female cynomolgus and rhesus macaques either cooperating or sedated were compared. All cytokines except TNFα demonstrated acceptable sensitivity and precision, with variable recovery and linearity. IFNγ, IL-2, IL-5, IL-6, IL-8, IL-12/23 (p40), IL-13, IL-15, MCP-1, TGFα, VEGF met acceptance criteria; G-CSF, IL-4, IL-10, MIP1α, sCD40L were marginal. Higher cytokine levels were observed in females and cytokine levels were blunted in sedated NHPs when compared to awake cooperating NHPs. Significant differences observed in cytokines related to sex, species, or imposed by handling highlight the importance of model design on translational relevance for clinical settings.